Hydrophobic modified PVC wood-plastic composite material and preparation method thereof

By adding nanosilicon dioxide microspheres covered with affinity toughening materials to the PVC wood-plastic composite, the problem of poor waterproof and moisture-proof performance of existing materials is solved, and higher waterproof and moisture-proof performance and use resistance are achieved.

CN119875261AInactive Publication Date: 2025-04-25ANHUI KOJO NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411973394.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing PVC wood-plastic composite materials have poor waterproof and moisture-proof performance, which leads to the problem of corrosion and cracking in home applications.

Method used

The hydrophobic properties of the material are improved by adding nanosilicon dioxide microspheres surface coated with affinity toughening material to the PVC wood-plastic composite. The nanosilica microspheres are treated by hydroxylation and coupling and are coated with a blend of ABS and carbon nanotubes on the surface to improve their dispersion and resistance.

Benefits of technology

It significantly improves the waterproof and moisture-proof performance of PVC wood-plastic composite materials, improves its use resistance, and enhances its application advantages in the home field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005219925120000091
    Figure BDA0005219925120000091
  • Figure BDA0005219925120000101
    Figure BDA0005219925120000101
  • Figure BDA0005219925120000102
    Figure BDA0005219925120000102
Patent Text Reader

Abstract

The invention provides a hydrophobic modified PVC wood-plastic composite material and a preparation method thereof, and relates to the technical field of PVC wood-plastic composites.The composite material is prepared from, by weight, 100-130 parts of PVC resin, 30-50 parts of wood flour, 15-30 parts of calcium carbonate, 15-20 parts of a hydrophobic agent, 5-10 parts of a stabilizer, 1-6 parts of a dispersing agent, 1-6 parts of a foaming agent, 1-2 parts of a coupling agent and 1-4 parts of a lubricating agent; the hydrophobic agent is a nano silicon dioxide microsphere of which the surface is coated with an affinity toughening material. The nano silicon dioxide microspheres coated with the affinity toughening material on the surface are added into a PVC wood-plastic composite material system, the nano silicon dioxide microspheres have excellent hydrophobic performance, and the waterproof and moisture-proof performance of the PVC wood-plastic composite material can be enhanced by adding the nano silicon dioxide microspheres. The modified coating of the affinity toughening material is beneficial to reducing the non-specific adsorption of the nano silicon dioxide microspheres and improving the defect that the nano silicon dioxide microspheres are easy to agglomerate, and also can improve the characteristic of brittleness of the nano silicon dioxide microspheres, so that the use tolerance of the nano silicon dioxide microspheres is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wood-plastic composite materials, and in particular to a hydrophobically modified PVC wood-plastic composite material and a preparation method thereof. Background Art

[0002] Wood plastic composite (WPC) is a new type of composite material made of wood as the main raw material (in the form of wood powder, sawdust, wood chips, bamboo chips, rice husks, wheat straw, soybean skin, peanut shells, bagasse, cotton straw, etc.), which is properly treated and mixed with various plastics (thermoplastic plastics used for wood plastic composites are mainly polyvinyl chloride, polyethylene, polypropylene, polystyrene, methyl methacrylate) in a certain proportion and added with special additives, such as coupling agents, dispersants, plasticizers, lubricants, heat stabilizers, colorants, flame retardants, mildew inhibitors, etc., through high temperature, extrusion, molding and other processes. It is a high-performance, high-value-added green and environmentally friendly composite material with excellent performance, wide application, green and environmental protection, and broad development prospects. PVC wood plastic composite is the main type of wood plastic composite material, that is, a composite material formed by processing polyvinyl chloride (PVC) and plant fiber materials (usually wood powder).

[0003] PVC wood-plastic composite materials can be used in various panels, such as wall panels, floors and other home furnishing fields. The waterproof and moisture-proof performance of PVC wood-plastic composite materials used in the home furnishing field is required to be high. This is because PVC wood-plastic panels are inevitably exposed to water stains during long-term use. If the waterproof performance of PVC wood-plastic panels is poor, the panels are prone to corrosion, cracking and other problems, which seriously affect the service life of the panels.

[0004] Based on this, the present invention discloses a hydrophobically modified PVC wood-plastic composite material and a preparation method thereof, which improves the hydrophobicity of the PVC wood-plastic composite material, effectively enhances the waterproof, moisture-proof and anti-corrosion properties of the PVC wood-plastic composite material, and enhances its advantages in application in the field of home furnishing. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the deficiencies of the prior art, the present invention provides a hydrophobically modified PVC wood-plastic composite material and a preparation method thereof, which solves the technical problem that the prior PVC wood-plastic composite material has poor waterproof and moisture resistance.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] The hydrophobic modified PVC wood-plastic composite material comprises the following materials in parts by weight: 100-130 parts of PVC resin, 30-50 parts of wood powder, 15-30 parts of calcium carbonate, 15-20 parts of hydrophobic agent, 5-10 parts of stabilizer, 1-6 parts of dispersant, 1-6 parts of foaming agent, 1-2 parts of coupling agent and 1-4 parts of lubricant; the hydrophobic agent is nano silicon dioxide microspheres with affinity toughening material coated on the surface.

[0010] Preferably, the affinity toughening material is a blend of ABS and carbon nanotubes, and the weight of the carbon nanotubes accounts for 5-10% of the total weight of the affinity toughening material.

[0011] Preferably, the mass ratio of the affinity toughening material to the nano-silica microspheres is 1:(7-9).

[0012] Preferably, the particle size of the nano-silica microspheres coated with the affinity toughening material is 30-70 nm.

[0013] Preferably, the preparation method of the microspheres is:

[0014] 1) Hydroxylation treatment of microsphere surface:

[0015] The untreated nano-silica microspheres are immersed in a sodium hydroxide solution, stirred and heated to 85-95°C, reacted for 0.5-0.8h, and a mixture of surface hydroxylated microspheres and the sodium hydroxide solution is obtained. The suspended microspheres are washed to neutrality, and then dried to obtain surface hydroxylated microsphere powder.

[0016] 2) Surface coupling treatment of hydroxylated microspheres:

[0017] Add the surface hydroxylated microsphere powder to 80% ethanol solution, stir and heat to 85-95°C, then add vinyl triethoxysilane, n-octyl triethoxysilane and maleic anhydride grafted polyethylene, continue the reaction for 3-4 hours, filter and dry to obtain coupled microspheres;

[0018] 3) Surface coating treatment of coupled microspheres:

[0019] The blend of ABS and carbon nanotubes is uniformly sprayed on the surface of the surface-coupled microspheres, and the product is obtained after drying.

[0020] Preferably, the untreated nano-silica microspheres are pre-treated by:

[0021] Take an appropriate amount of nano-silica microspheres and soak them in an ethanol solution. After ultrasonic stirring, let the solution stand for separation, filter out damaged microspheres, and then dry the undamaged microspheres for later use.

[0022] Preferably, the surface of the hydroxylated microsphere powder is rough and grooved, and the surface of the coated product is uniform and smooth, and the cross-section of the coating layer has hollow channels.

[0023] Preferably, the dispersant is a mixture of any one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphate, sodium dodecyl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide, and fatty acid polyethylene glycol esters.

[0024] Preferably, the stabilizer is a calcium zinc stabilizer or an organic tin stabilizer.

[0025] Preferably, the foaming agent is azodicarbonamide or calcium bicarbonate.

[0026] Preferably, the coupling agent is titanate or aluminate.

[0027] Preferably, the lubricant is Westrchem STR-850.

[0028] The preparation method of the hydrophobically modified PVC wood-plastic composite material comprises the following specific steps:

[0029] First, heat the PVC resin to a molten state, stir it evenly, then add wood powder, calcium carbonate, hydrophobic agent and dispersant, and mix the above components evenly;

[0030] Then, a stabilizer, a foaming agent, a coupling agent and a lubricant are added to the mixed system and stirred to react;

[0031] After the reaction is completed, the PVC wood-plastic composite material is melt-extruded, pressed into shape, crushed and sieved to obtain a finished product.

[0032] (III) Beneficial effects

[0033] The present invention provides a hydrophobically modified PVC wood-plastic composite material and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention adds nano-silica microspheres coated with affinity toughening materials on the surface to the PVC wood-plastic composite material system. The nano-silica microspheres themselves have excellent hydrophobic properties, and the addition of the nano-silica microspheres is conducive to enhancing the waterproof and moisture-proof properties of the PVC wood-plastic composite material. The modified coating of the affinity toughening material is conducive to reducing the non-specific adsorption of the nano-silica microspheres, improving the defect of easy agglomeration, and also improving the brittle properties of the nano-silica microspheres themselves, further improving the use tolerance of the nano-silica microspheres. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The embodiment of the present application solves the technical problem of poor waterproof and moisture-proof properties of existing PVC wood-plastic composite materials by providing a hydrophobically modified PVC wood-plastic composite material and a preparation method thereof.

[0037] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.

[0038] The raw materials disclosed in the technical solution of the present invention are all purchased from cooperative manufacturers.

[0039] Embodiment 1:

[0040] The hydrophobically modified PVC wood-plastic composite material comprises the following materials in parts by weight: 100 parts of PVC resin, 30 parts of wood powder, 15 parts of calcium carbonate, 15 parts of nano-silicon dioxide microspheres with a particle size of 30-70 nm and a surface coated with a blend of ABS and carbon nanotubes, 5 parts of a calcium zinc stabilizer, 1 part of sodium tripolyphosphate, 1 part of azodicarbonamide, 1 part of titanate, and 1 part of Westrchem STR-850.

[0041] The weight of the carbon nanotubes accounts for 5% of the total weight of the affinity toughening material.

[0042] The mass ratio of the ABS and carbon nanotube blend to the nano-silica microspheres is 1:7.

[0043] The preparation method of the hydrophobically modified PVC wood-plastic composite material comprises the following specific steps:

[0044] S1. Pretreatment of Nano-Silica Microspheres:

[0045] Take an appropriate amount of nano-silica microspheres and soak them in an ethanol solution. After ultrasonication for 10 minutes, let the solution stand and separate. Filter out the damaged microspheres. Then, place the undamaged microspheres in a 100°C oven for drying and set aside.

[0046] S2. Preparation of nano-silica microspheres coated with ABS and carbon nanotube blends:

[0047] 1) Hydroxylation treatment of microsphere surface:

[0048] The untreated nano-silica microspheres were immersed in a 0.5 mol / L sodium hydroxide solution, stirred and heated to 85°C, and reacted for 0.8 h to obtain a mixture of surface hydroxylated microspheres and the sodium hydroxide solution. The suspended microspheres were washed to neutrality and then placed in a 100°C oven for drying to obtain surface hydroxylated microsphere powders.

[0049] 2) Surface coupling treatment of hydroxylated microspheres:

[0050] The surface hydroxylated microsphere powder was added to 80% ethanol solution, and 2wt% vinyl triethoxysilane, 1.1wt% n-octyl triethoxysilane and 0.7wt% maleic anhydride grafted polyethylene were added when the solution was stirred and heated to 85°C, and the reaction was continued for 4h, and the coupled microspheres were obtained by suction filtration and drying. The coupled microspheres had a rough and grooved surface under an electron microscope.

[0051] 3) Surface coating treatment of coupled microspheres:

[0052] The blend of ABS and carbon nanotubes is uniformly sprayed on the surface of the surface-coupled microspheres, and a product is obtained after drying. The surface of the product is uniform and smooth under an electron microscope, and a hollow channel is formed on the coating layer of the cross section due to the addition of carbon nanotubes.

[0053] S3. Preparation of hydrophobically modified PVC wood-plastic composites:

[0054] First, heat the PVC resin to a molten state, stir it evenly, then add wood powder, calcium carbonate, nano-silicon dioxide microspheres coated with a blend of ABS and carbon nanotubes, and sodium tripolyphosphate, and mix the above components evenly;

[0055] Then, calcium zinc stabilizer, Westrchem STR-850, azodicarbonamide and titanate were added to the mixed system, and stirred to react;

[0056] After the reaction is completed, the PVC wood-plastic composite material is melt-extruded, pressed into shape, crushed and sieved to obtain a finished product.

[0057] Embodiment 2:

[0058] The hydrophobically modified PVC wood-plastic composite material comprises the following materials in parts by weight: 115 parts of PVC resin, 40 parts of wood powder, 22 parts of calcium carbonate, 16 parts of nano-silicon dioxide microspheres with a particle size of 30-70 nm and a surface coated with a blend of ABS and carbon nanotubes, 7 parts of an organic tin stabilizer, 4 parts of sodium dodecyl sulfate, 3 parts of calcium bicarbonate, 1.5 parts of titanate, and 2 parts of Westrchem STR-850.

[0059] The weight of the carbon nanotubes accounts for 8% of the total weight of the affinity toughening material.

[0060] The mass ratio of the ABS and carbon nanotube blend to the nano-silica microspheres is 1:8.

[0061] The preparation method of the hydrophobically modified PVC wood-plastic composite material comprises the following specific steps:

[0062] S1. Pretreatment of Nano-Silica Microspheres:

[0063] Take an appropriate amount of nano-silica microspheres and soak them in an ethanol solution. After ultrasonication for 10 minutes, let the solution stand and separate. Filter out the damaged microspheres. Then, place the undamaged microspheres in a 100°C oven for drying and set aside.

[0064] S2. Preparation of nano-silica microspheres coated with ABS and carbon nanotube blends:

[0065] 1) Hydroxylation treatment of microsphere surface:

[0066] The untreated nano-silica microspheres were immersed in a 0.5 mol / L sodium hydroxide solution, stirred and heated to 90°C, and reacted for 0.6 h to obtain a mixture of surface hydroxylated microspheres and the sodium hydroxide solution. The suspended microspheres were washed to neutrality and then placed in a 100°C oven for drying to obtain surface hydroxylated microsphere powders.

[0067] 2) Surface coupling treatment of hydroxylated microspheres:

[0068] The surface hydroxylated microsphere powder was added to 80% ethanol solution, and 2wt% vinyl triethoxysilane, 1.1wt% n-octyl triethoxysilane and 0.7wt% maleic anhydride grafted polyethylene were added when the solution was heated to 90°C with stirring, and the reaction was continued for 3.5h, and the coupled microspheres were obtained by suction filtration and drying. The coupled microspheres had a rough and grooved surface under an electron microscope.

[0069] 3) Surface coating treatment of coupled microspheres:

[0070] The blend of ABS and carbon nanotubes is uniformly sprayed on the surface of the surface-coupled microspheres, and a product is obtained after drying. The surface of the product is uniform and smooth under an electron microscope, and a hollow channel is formed on the coating layer of the cross section due to the addition of carbon nanotubes.

[0071] S3. Preparation of hydrophobically modified PVC wood-plastic composites:

[0072] First, heat the PVC resin to a molten state, stir it evenly, then add wood powder, calcium carbonate, nano-silicon dioxide microspheres coated with a blend of ABS and carbon nanotubes, and sodium dodecyl sulfate, and mix the above components evenly;

[0073] Then, an organic tin stabilizer, calcium bicarbonate, titanate, and Westrchem STR-850 are added to the mixed system, and stirred to react;

[0074] After the reaction is completed, the PVC wood-plastic composite material is melt-extruded, pressed into shape, crushed and sieved to obtain a finished product.

[0075] Example 3

[0076] The hydrophobically modified PVC wood-plastic composite material comprises the following materials in parts by weight: 130 parts of PVC resin, 50 parts of wood powder, 30 parts of calcium carbonate, 20 parts of nano-silicon dioxide microspheres with a particle size of 30-70 nm and a surface coated with a blend of ABS and carbon nanotubes, 10 parts of an organic tin stabilizer, 6 parts of polyacrylamide, 6 parts of azodicarbonamide, 2 parts of aluminate, and 4 parts of Westrchem STR-850.

[0077] The weight of the carbon nanotubes accounts for 10% of the total weight of the affinity toughening material.

[0078] The mass ratio of the ABS and carbon nanotube blend to the nano-silica microspheres is 1:9.

[0079] The preparation method of the hydrophobically modified PVC wood-plastic composite material comprises the following specific steps:

[0080] S1. Pretreatment of Nano-Silica Microspheres:

[0081] Take an appropriate amount of nano-silica microspheres and soak them in an ethanol solution. After ultrasonication for 10 minutes, let the solution stand and separate. Filter out the damaged microspheres. Then, place the undamaged microspheres in a 100°C oven for drying and set aside.

[0082] S2. Preparation of nano-silica microspheres coated with ABS and carbon nanotube blends:

[0083] 1) Hydroxylation treatment of microsphere surface:

[0084] The untreated nano-silica microspheres were immersed in a 0.5 mol / L sodium hydroxide solution, heated to 95°C with stirring, and reacted for 0.5 h to obtain a mixture of surface hydroxylated microspheres and the sodium hydroxide solution. The suspended microspheres were washed to neutrality and then placed in a 100°C oven for drying to obtain surface hydroxylated microsphere powders.

[0085] 2) Surface coupling treatment of hydroxylated microspheres:

[0086] The surface hydroxylated microsphere powder was added to 80% ethanol solution, and 2wt% vinyl triethoxysilane, 1.1wt% n-octyl triethoxysilane and 0.7wt% maleic anhydride grafted polyethylene were added when the solution was stirred and heated to 95°C, and the reaction was continued for 3h, and the coupled microspheres were obtained by suction filtration and drying. The coupled microspheres had a rough and grooved surface under an electron microscope.

[0087] 3) Surface coating treatment of coupled microspheres:

[0088] The blend of ABS and carbon nanotubes is uniformly sprayed on the surface of the surface-coupled microspheres, and a product is obtained after drying. The surface of the product is uniform and smooth under an electron microscope, and a hollow channel is formed on the coating layer of the cross section due to the addition of carbon nanotubes.

[0089] S3. Preparation of hydrophobically modified PVC wood-plastic composites:

[0090] First, heat the PVC resin to a molten state, stir it evenly, then add wood powder, calcium carbonate, nano-silicon dioxide microspheres coated with a blend of ABS and carbon nanotubes, and polyacrylamide, and mix the above components evenly;

[0091] Then, an organic tin stabilizer, azodicarbonamide, aluminate, and Westrchem STR-850 were added to the mixed system, and stirred to react;

[0092] After the reaction is completed, the PVC wood-plastic composite material is melt-extruded, pressed into shape, crushed and sieved to obtain a finished product.

[0093] Comparative Example 1 is different from Example 2 in that:

[0094] Remove the hydrophobic agent in the PVC wood plastic composite system.

[0095] Comparative Example 2 is different from Example 2 in that:

[0096] Remove the hydrophobic agent in the PVC wood plastic composite system.

[0097] Comparative Example 3 is different from Example 2 in that:

[0098] The surface of the nano-silica microspheres was only modified by hydroxylation and coupling, and no coating was performed. The difference between Comparative Example 4 and Example 2 is that:

[0099] The surface of the nano-silica microspheres is only coated with carbon nanotubes.

[0100] Comparative Example 5 is different from Example 2 in that:

[0101] The surface of nano-silica microspheres is only coated with ABS.

[0102] Comparative Example 6 is different from Example 2 in that:

[0103] The surface of nano-silica microspheres is coated with PC and carbon nanotubes.

[0104] Comparative Example 7 is different from Example 2 in that:

[0105] The surface of nano-silica microspheres is coated with ABS and PC.

[0106] Comparative Example 8 is different from Example 2 in that:

[0107] The carbon nanotubes account for 3% of the total weight of the surface affinity and adhesion-promoting material.

[0108] Comparative Example 9 is different from Example 2 in that:

[0109] The carbon nanotubes account for 15% of the total weight of the surface affinity adhesion-promoting material.

[0110] Comparative Example 10 is different from Example 2 in that:

[0111] The mass ratio of the surface affinity adhesion enhancing material to the nano-silica microspheres is 1:6.

[0112] Comparative Example 11 is different from Example 2 in that:

[0113] The mass ratio of the surface affinity adhesion enhancing material to the nano-silica microspheres is 1:10.

[0114] Comparative Example 12 is different from Example 2 in that:

[0115] The nano-silica microspheres are not subjected to hydroxylation treatment, but only to coupling treatment.

[0116] Comparative Example 13 is different from Example 2 in that:

[0117] The nano-silica microspheres were only subjected to hydroxylation treatment without coupling treatment.

[0118] Comparative Example 14 is different from Example 2 in that:

[0119] Remove the maleic anhydride grafted polyethylene used in the coupling treatment.

[0120] Comparative Example 15 is different from Example 2 in that:

[0121] The n-octyltriethoxysilane used in the coupling treatment was deleted.

[0122] Comparative Example 16 is different from Example 2 in that:

[0123] Vinyltriethoxysilane used in the coupling treatment was replaced with γ-aminopropyltriethoxysilane.

[0124] Comparative Example 17 is different from Example 2 in that:

[0125] The n-octyltriethoxysilane used in the coupling treatment was replaced with γ-aminopropyltriethoxysilane.

[0126] Performance test data

[0127] 1. Samples of the hydrophobically modified PVC wood-plastic composite materials prepared by the methods of Examples 1-3 and Comparative Examples 1-17 were taken, and the following performance tests were performed on each group of samples:

[0128] 1) Tensile properties:

[0129] According to the standard test of GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles", the tensile speed is 50mm / min, the narrowest size of the dumbbell-shaped standard specimen is 10mm×4mm, 6 specimens are tested and the average is taken.

[0130] 2) Impact strength:

[0131] Impact performance: tested according to GB / T 1843-2008 "Determination of cantilever beam impact strength of plastics", the sample size is 80mm×10mm×4mm, 6 samples are tested and the average value is taken.

[0132] 3) Waterproof performance:

[0133] According to GB / T24508-2020 standard, the water absorption thickness expansion rate of the sample is tested. The smaller the water absorption thickness expansion rate of the wood-plastic composite material, the higher the moisture-proof performance of the floor.

[0134] Table 1 - Performance test data of samples

[0135]

[0136]

[0137] 2. The dispersion uniformity of the hydrophobic agent samples prepared by the methods of Examples 1-3 and Comparative Examples 2-17 in the PVC wood-plastic composite material system was observed using a scanning electron microscope, and the observation results were recorded in Table 2:

[0138] Table 2-Observation results of the uniform dispersion performance of the hydrophobic agent

[0139]

[0140]

[0141] From the test data in Table 1 and Table 2, it can be seen that:

[0142] 1) The technical solutions of the present invention disclosed in Examples 1-3, after adding a hydrophobic agent to the PVC wood-plastic composite material system, are compared with the technical solution of Comparative Example 1, and since the nano-silica particles of the present invention are surface modified and coated, their mechanical properties are also significantly improved.

[0143] 2) The data of Example 2 and Comparative Examples 2-6 show that the use of a blend of ABS and carbon nanotubes for surface coating has a significant promoting effect on improving the mechanical properties of PVC wood-plastic composite materials, and after replacing ABS or carbon nanotubes with PC, the mechanical properties have a certain degree of decline. From the water absorption data, it can be seen that the coating on the surface of the nano-silica microspheres will also have a certain impact on the waterproof performance of the PVC wood-plastic composite system. The possible reason is that after coating with the affinity material, the non-specific adsorption of the nano-silica microspheres is improved, and the dispersion uniformity of the microspheres is improved, thereby improving its waterproof performance.

[0144] 3) The data of Example 2 and Comparative Examples 7-10 show that the total weight of carbon nanotubes in the affinity toughening material and the mass ratio of the affinity toughening material to the nano-silica microspheres need to be controlled within an appropriate range so that the hydrophobic agent microspheres can maximize their effectiveness.

[0145] 4) The data of Example 2 and Comparative Examples 11-13 show that whether the surface of the nano-silica microspheres is hydroxylated or coupled will affect the waterproof performance of the PVC wood-plastic composite material system. This may be because modifying the surface of the nano-silica microspheres can improve the defects of the nano-silica microspheres themselves to a certain extent, thereby improving their hydrophobic and toughening properties in the system.

[0146] 5) The data of Example 2 and Comparative Examples 14-17 show that the performance of the coupled microspheres obtained by coupling the nano-silica microspheres with different coupling agents and compatibilizers will be significantly different, which also shows that there is a synergistic effect between the three components of vinyl triethoxysilane, n-octyl triethoxysilane and maleic anhydride grafted polyethylene. Vinyl triethoxysilane is suitable for surface modification of silicon-containing fillers and can effectively improve the binding force between silicon-containing fillers and polyolefin resins. N-octyl triethoxysilane is suitable for treating silicon dioxide and can effectively improve the compatibility and dispersibility of silicon dioxide in resins. Maleic anhydride grafted polyethylene is used to improve the nonspecific adsorption on the surface of nano-silica particles and enhance their interfacial compatibility.

[0147] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0148] 1. The present invention adds nano-silica microspheres coated with affinity toughening materials to the PVC wood-plastic composite material system. The nano-silica microspheres themselves have excellent hydrophobic properties, and their addition is conducive to enhancing the waterproof and moisture-proof properties of the PVC wood-plastic composite material. The modified coating of the affinity toughening material is conducive to reducing the nonspecific adsorption of the nano-silica microspheres, improving the defect of easy agglomeration, and also improving the brittle properties of the nano-silica microspheres themselves, further improving the use tolerance of the nano-silica microspheres.

[0149] 2. The present invention selects ABS and carbon nanotubes as affinity toughening materials, not only because of the properties of ABS and carbon nanotubes themselves, but also because during the spraying process, carbon nanotubes will form hollow channels on the surface of nano-silica microspheres, similar to the "carbon skeleton" structure. Part of ABS can be filled in the "carbon skeleton", which is beneficial to improve the brittle defect of nano-silica.

[0150] 3. The present invention performs hydroxylation and coupling modification on the surface of nano-silica microspheres. The three components of vinyl triethoxysilane, n-octyl triethoxysilane and maleic anhydride grafted polyethylene used in the coupling modification have a synergistic effect, which can effectively improve the compatibility of nano-silica and the adsorption of affinity toughening materials, thereby improving the overall performance of the hydrophobically modified nano-silica microspheres, and further improving its performance in the PVC wood-plastic composite material system.

[0151] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0152] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hydrophobically modified PVC wood-plastic composite material, characterized in that: The invention comprises the following materials in parts by weight: 100-130 parts of PVC resin, 30-50 parts of wood flour, 15-30 parts of calcium carbonate, 15-20 parts of hydrophobic agent, 5-10 parts of stabilizer, 1-6 parts of dispersant, 1-6 parts of foaming agent, 1-2 parts of coupling agent and 1-4 parts of lubricant; the hydrophobic agent is nano silicon dioxide microspheres with the surface coated with affinity toughening material.

2. The hydrophobically modified PVC wood-plastic composite material according to claim 1, characterized in that: The affinity toughening material is a blend of ABS and carbon nanotubes, and the weight of the carbon nanotubes accounts for 5-10% of the total weight of the affinity toughening material.

3. The hydrophobically modified PVC wood-plastic composite material according to claim 1, characterized in that: The mass ratio of the affinity toughening material to the nano-silicon dioxide microspheres is 1:(7-9).

4. The hydrophobically modified PVC wood-plastic composite material according to claim 1, characterized in that: The particle size of the nano silicon dioxide microspheres coated with the affinity toughening material is 30-70 nm.

5. The hydrophobically modified PVC wood-plastic composite material according to claim 2, characterized in that: The preparation method of the microspheres is: 1) Hydroxylation treatment of microsphere surface: The untreated nano-silica microspheres are immersed in a sodium hydroxide solution, stirred and heated to 85-95°C, reacted for 0.5-0.8h, and a mixture of surface hydroxylated microspheres and the sodium hydroxide solution is obtained. The suspended microspheres are washed to neutrality, and then dried to obtain surface hydroxylated microsphere powder. 2) Surface coupling treatment of hydroxylated microspheres: Add the surface hydroxylated microsphere powder to 80% ethanol solution, stir and heat to 85-95°C, then add vinyl triethoxysilane, n-octyl triethoxysilane and maleic anhydride grafted polyethylene, continue the reaction for 3-4 hours, filter and dry to obtain coupled microspheres; 3) Surface coating treatment of coupled microspheres: The blend of ABS and carbon nanotubes is uniformly sprayed on the surface of the surface-coupled microspheres, and the product is obtained after drying.

6. The hydrophobically modified PVC wood-plastic composite material according to claim 5, characterized in that: The untreated nano-silica microspheres are pre-treated by: Take an appropriate amount of nano-silica microspheres and soak them in an ethanol solution. After ultrasonic stirring, let the solution stand for separation, filter out damaged microspheres, and then dry the undamaged microspheres for later use.

7. The hydrophobically modified PVC wood-plastic composite material according to claim 5, characterized in that: The surface of the hydroxylated microsphere powder is rough and grooved, and the surface of the coated product is uniform and smooth, and the cross-section of the coating layer has hollow channels.

8. The hydrophobically modified PVC wood-plastic composite material according to claim 1, characterized in that: The dispersant is a mixture of any one or more of sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, cellulose derivatives, polyacrylamide, and fatty acid polyethylene glycol ester.

9. The method for preparing the hydrophobically modified PVC wood-plastic composite material according to any one of claims 1 to 8, characterized in that: The specific steps are: First, heat the PVC resin to a molten state, stir it evenly, then add wood powder, calcium carbonate, hydrophobic agent and dispersant, and mix the above components evenly; Then, a stabilizer, a foaming agent, a coupling agent and a lubricant are added to the mixed system and stirred to react; After the reaction is completed, the PVC wood-plastic composite material is melt-extruded, pressed into shape, crushed and sieved to obtain a finished product.

Citation Information

Patent Citations

  • High-intensity wood-plastic composite

    CN106243761A

  • Aerogel PVC wood-plastic composite material and preparation method thereof

    CN117247644A

  • Wood-plastic plate based on hydrophobic modified wood flour and preparation method

    CN118440433A

  • PVC nanocomposite manufacturing technology and applications

    US20080194736A1

  • Antibacterial PVC wood-plastic multilayer composite material and preparation method therefor

    WO2023201854A1